Reversible Data Hiding Technique using Novel Interpolation Technique and Discrete Cosine Transform - Sah, Basant; Jha, Vijay Kumar (International Journal of Integrated Engineering, 2019)
The application of internet has expanded colossally in recent years. Subsequently, security of data has turned out to be a quite important factor to focus. It is likewise discernible that over the internet, data can be controlled, cautioned or compromised. To overcome these issues numerous methodologies are proposed. These methods depend on some type of mechanism, where data is encoded and with the help of a key message and using the key it can be recovered the receiver. In pictures, reversible data hiding (RDH) is a strategy which is exceptionally useful in regaining original cover after the embedded message is separated. This key strategy is comprehensively utilized as a piece of medical imagery, law crime scene investigation and military symbolism, where no distortion of the cover is allowed. Because of being reversible, RDH has pulled in great research interest. This paper discusses an improvement in RDH technique while also considering DCT based compression technique for further improvements. Simulation has been carried out to evaluate the performance in terms of Peak-to-Signal Noise Ratio (PSNR) and Structural Similarity Index (SSIM). It has been found that our proposed method performs better than earlier methods.